Определение 4-метил-2,6-диизоборнилфенола и его метаболитов в биологических образцах методом ВЭЖХ-МС/МС - Лакеев, Александр Павлович (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
Dibornol (4-methyl-2,6-diisobornylphenol, IBP) is a semi-synthetic, nontoxic phenolic antioxidant with neuro- and cardioprotective properties. In this regard, IBP has attracted considerable attention in recent years in Russia. Currently, there are no validated analytical methods that allowed the simultaneous determination of IBP and its metabolites (3,5-diisobornyl-4-hydroxybenzyl alcohol, IBP–OH; 3,5-diisobornyl-4- hydroxybenzaldehyde, IBP–CHO) in various biological samples. Therefore, the aim of the present study was to develop and validate a simple and sensitive HPLC–MS/MS method for quantification of IBP, IBP–OH and IBP–CHO in rat plasma. The liquid-liquid extraction technique using MTBE, hexane and diethyl ether (50:37.5:12.5, v/v/v) was adapted for taking out the analytes from the matrix. The separation was conducted using C18 column at 40°C under isocratic elution with 5 mM HCOONH4 in water (A) and CH3CN (B) mobile phases (3:97, v/v, respectively). The flow rate was 0.25 ml/min with a total analysis time of 3.50 min. IBP–OH, IBP–CHO and IBP were eluted at 1.39 ± 0.02, 1.69 ± 0.03 and 2.65 ± 0.02 min, respectively. Butylated hydroxytoluene was used as an internal standard. The analytes were identified using multiple reaction monitoring scans in negative polarity mode. The ion transitions were set at m/z 395.1 → 377.4 (IBP–OH), 393.2 → 270.1 (IBP–CHO) and 379.1 → 256.3 (IBP). The developed method was successfully applied to pharmacokinetic studies of the IBP–OH, IBP–CHO and IBP in rats after a single oral dose of IBP (10 mg/kg).